Prospects for the Development of Halal Culinary MSMEs in Encouraging Sustainable Business - HS, Sufyati; Resti, Anggi Angga; Matondang, Nurhafifah; Ridwansyah, Muhamad; Priyatna, Muhammad Randhika (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2024)
Sustainable business refers to business practices that pay attention to social and environmental impacts in addition to financial returns. This research was conducted in Depok, West Java, as a satellite city of Jakarta, with a focus on halal culinary development. The factors studied include Halal Certification, Halal Practice Compliance, Green Marketing, and Performance of Halal Culinary MSMEs. Halal Culinary MSMEs ensure that all processes and ingredients comply with Islamic sharia principles, important for consumer confidence and improving the performance of the halal industry. The research objective is to measure the performance of Culinary MSMEs through halal certification, halal practice compliance, and green marketing. The research method uses a quantitative descriptive approach with a questionnaire to MSME players in Depok and data analysis using SmartPLS. The results showed that halal certification and green marketing have a positive and significant effect on the performance of culinary MSMEs in Depok, while compliance with halal practices has a positive but insignificant effect. Recommendations include improving halal certification access and processes, education on halal practice compliance, and effective green marketing strategies to support sustainable halal culinary development.